2006
DOI: 10.1097/00024665-200601000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Computer Use in an Urban University Hospital

Abstract: The linkage of patient safety and care quality to the implementation of computerized information systems assumes that clinical staff are skilled with computers. Nurses and nursing support staff increasingly require computers to carry out their work. Minimum computer competencies for nurses have been identified. The determination of whether the current nursing workforce has acquired these competencies remains uncertain. We administered a self-assessment survey to nurses and nursing support staff to determine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…2002). Wilbright et al. (2006), in a study of nurses’ self‐assessment of work‐related computer skills, noted that 28% of the 454 nurses and nursing support staff rated themselves as having poor or fair proficiency, with a tendency for respondents aged over 50 years or graduating before 1984 to rate themselves as lower in proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…2002). Wilbright et al. (2006), in a study of nurses’ self‐assessment of work‐related computer skills, noted that 28% of the 454 nurses and nursing support staff rated themselves as having poor or fair proficiency, with a tendency for respondents aged over 50 years or graduating before 1984 to rate themselves as lower in proficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these practitioners will have completed their education before information technology became imbedded in everyday activities. A study of nurses’ work‐related computer skills found 28% of the total group (454 nurses and nursing support staff) self‐assessed as poor or fair proficiency; nurses 50 years or over or graduating before 1984 rated themselves as lower in proficiency (Wilbright et al. (2006).…”
Section: Discussionmentioning
confidence: 99%
“…6 Ten years later, NURSING ADMINISTRATION QUARTERLY/JULY-SEPTEMBER 2009 a study shows nurses continue to lack the computer skills required to work efficiently and effectively in a hospital setting. 7 The computer age is here to stay. Nurses will best serve themselves and their clients if they embrace the technological tools available.…”
Section: Key Strategy #1: Get Comfortable With Technology Yourselfmentioning
confidence: 99%